The 1982 Law of the Sea Convention at 30 : Successes, Challenges and New Agendas - Freestone, David (Martinus Nijhoff Publishers, 2013)
The 1982 Law of the Sea Convention at 30: Successes, Challenges and New Agendas offers twenty essays by renowned Law of the Sea scholars, published to mark the 30th Anniversary of the adoption of the 1982 UNConvention on the Law of the Sea.